"Install Freedom Now!" Choosing not to Communicate with Digital Media at Work and Home - Hartmann, Maren (Javnost-The Public, 2022)
The emphasis in this article is on the freedom to communicate, which differs from both the right to communicate and communication rights. Instead of focussing directly on the freedom to communicate, the path taken instead is an emphasis on (digital) “non-communication.” This is subsequently expanded to a freedom not to communicate. The article begins with a cursory theoretical definition of communicative freedom, based on the notions of communicative action, social justice and reciprocal recognition. It then turns to a range of examples of “non-communication.” These stretch from corporate environments and their attempts to introduce “non-communication” top-down (mostly via time-based restrictions of the use of company-related communication tools) via the experience of a “digital diet” workshop at the university to instances of “digital detox,” which are offered on the life-improvement markets today. Through these examples, the question of the freedom not to communicate will be explored. Most of the examples underline the many current limitations of this freedom to communicate. The tentative alternative suggested is a new version of distant proximity, enacted through temporary dis-connectivity. This, so the claim, is needed to resist the growing framework of constant connectivity that we are constantly confronted within both private and working lives.